(untitled) (Bangladesh Journal of Botany, 2026)
A newtaxa, Androsace armeniaca subsp. vulcanica Sefalı & Eroğlu nov. (Primulaceae) is described and illustrated from Ağrı Province, Türkiye. It is morphologically assigned to Androsace sect. Andrapsis based on its long scape and small flower habit and the presence of glandular hairs covering the calyx and scape. This new taxon closely resembles A. armeniaca subsp. armeniaca var. armeniaca and A. armeniaca subsp. armeniaca var. macrantha, but is easily distinguished by its overall habitus, smaller flowers, distinct corolla and calyx characteristics (including the color and lobe shape), pedicel length and habitat (volcanic areas). Bangladesh J. Bot. 55(1): 115-122, 2026 (March)